A Spoonful of Choice: How Allocation Increases Satisfaction with Tax Payments. (September 2013) - Lamberton, Cait
How can tax payment be made more satisfying? The author focuses on the low volition and collective nature of tax-funded benefits as primary causes of low satisfaction with tax payment. Three studies suggest that allowing people to allocate a small portion (in the present research, 10%) of their payment across budgets provided by the billing party both introduces an element of volition into the payment process and increases the perceived benefit associated with tax payment. As a result, the author concludes that taxpayers are significantly more satisfied with paying taxes when they allocate their payments, even if their payment amount remains completely unchanged. In addition to enhancing taxpayer satisfaction, an allocation program, if well implemented, could provide some hope for correcting existing lack of voice, address disconnects between spending and taxpayers' priorities, and increase civic engagement in general.